Intercultural Competence: Development and Validation of a Theoretical Framework, a Cross-Cultural Multimethod Test, and a Collaborative Assessment Intervention - Schnabel, Deborah Bianca Larissa (Universität Tübingen, 2015)
Globalization, migration, and international traffic have substantially raised the relevance of intercultural competence (ICC) in today’s world of work (Fantini, 2009; Leung, Ang, & Tan, 2014; Spitzberg & Changnon, 2009). This has also increased the demand for assessing and training individuals to enable them to handle their intercultural encounters while studying or working in an international context. Despite the existence of many definitions, models, and approaches to the measurement of ICC, the circular process of understanding, assessing, and training ICC has been understudied (Schnabel, Kelava, Seifert, & Kuhlbrodt, 2015). The interconnection between assessment and training calls for behavior-oriented characteristics that can actually be trained, whereas most of the ICC concepts are trait- and/or attitude-based (e.g., Multicultural Personality Model: Van der Zee & Van Oudenhoven, 2000; Developmental Model of Intercultural Sensitivity: Bennett, 1993). This monograph presents a novel ICC framework that was created by using a phenomenological expert-based strategy. The framework includes an ICC onion model, which organizes the various aspects of ICC. Malleable ability-based intercultural competences are located in the heart of this model, whereas traits, attitudes, or (cultural) intelligence are situated in an outer layer of the onion model. As competence is directly linked to performance (Erpenbeck, 2010), ICC is subsequently defined as a global behavioral orientation, which enables individuals to handle intercultural situations (Schnabel et al., 2015). Moreover, ICC is understood as a multidimensional construct in which multiple competences, together or separately, influence the quality of intercultural interaction. These competences were collected through exploratory expert interviews and literature research and empirically investigated in a pretest. The results are outlined in Chapter 3. Chapter 4 shows how the Test to Measure Intercultural Competence (TMIC; Schnabel et al., 2015) was developed on the basis of the preliminary model presented in Chapter 3. Even though there is a strong need for researchers to use more than one method to assess a complex construct such as ICC, there was no validated multimethod instrument that was available in the ICC field (Leung et al., 2014). To fill this gap, Schnabel et al. (2015) created a situational judgment test (TMIC-SJT) that complements a Likert-scale-based self-appraisal scale (TMIC-SA). Chapter 4 illustrates the design and results of two studies, one conducted with German students and the other one with German professionals. I show the satisfactory fit statistics of a first-order factor model with 17 factors, calculated with exploratory structural equation modeling (ESEM; Asparouhov & Muthén, 2009), and of a second-order factor model with six factors, calculated with confirmatory factor analysis. Evidence for construct and criterion validity as well as for the incremental validity of the TMIC-SJT is given. Chapter 5 reviews a newly designed brief training intervention that was based on collaborative assessment (Fischer, 1994, 2000). The benefits of taking part in the TMIC and receiving written feedback as well as a 1-hr collaborative test-feedback intervention for students going abroad are illustrated with the results of an experimental study (Schnabel, Kelava, & Van de Vijver, in press). There is a focus on self-reported ICC development, the stages of change (DiClemente & Prochaska, 1998; Prochaska, DiClemente, & Norcross, 1992), intercultural self-confidence, and intercultural self-understanding. Chapter 6 shows how a short version of the TMIC (TMIC-S; Schnabel, Kelava, Van de Vijver, & Seifert, 2014), particularly useful for employee selection purposes, was developed and tested in Germany and Brazil. Through the analysis of measurement invariance (Meredith, 1993), a cross-culturally valid model of ICC was supported. The overall discussion in Chapter 7 integrates the aforementioned subtopics of this monograph and describes the major implications and limitations. Additionally, I give a global outlook concerning future research topics in the ICC domain. Aktuelle Entwicklungen hinsichtlich der Globalisierung, der Migration und des internationalen Handelsverkehrs wirken sich unmittelbar auf die Bedeutung interkultureller Kompetenz in der heutigen Arbeitswelt aus (Fantini, 2009; Leung, Ang, & Tan, 2014; Spitzberg & Changnon, 2009). Der Bedarf an Mess- und Trainingsinstrumenten, die ein Individuum dabei unterstützen, interkulturelle Herausforderungen während des Studiums oder der Arbeit im internationalen Kontext zu meistern, wächst entsprechend. Zwar existieren bereits Definitionen, Modelle und Messansätze zur interkulturellen Kompetenz, jedoch wurde der zirkuläre Prozess aus Definition, Messung und Training von interkultureller Kompetenz in der Wissenschaft bislang vernachlässigt (Schnabel, Kelava, Seifert, & Kuhlbrodt, 2015). Die Vernetzung zwischen Messung und Training verlangt nach verhaltensorientierten Eigenschaften, die auch tatsächlich trainiert werden können. Die meisten bestehenden Konzepte basieren allerdings auf stabilen Persönlichkeitsmerkmalen und/oder Einstellungen (z. B. Multicultural Personality Model: Van der Zee & Van Oudenhoven, 2000; Developmental Model of Intercultural Sensitivity: Bennett, 1993). In dieser Monographie wird ein Rahmenkonzept interkultureller Kompetenz präsentiert, das mithilfe einer phänomenologisch-expertenbasierten Strategie entwickelt wurde. Das Rahmenkonzept enthält ein Zwiebelmodell interkultureller Kompetenz, das die unterschiedlichen Aspekte interkultureller Kompetenz organisiert. Veränderbare fähigkeitsbasierte interkulturelle Kompetenzen sind im Herzen des Modells angesiedelt, wohingegen Persönlichkeitsmerkmale, Einstellungen oder auch (kulturelle) Intelligenz in der äußeren Schicht lokalisiert sind. Da Kompetenz direkt an das Verhalten gekoppelt ist (Erpenbeck, 2010), wird interkulturelle Kompetenz folglich als globale Verhaltensorientierung definiert, die ein Individuum dazu befähigt, interkulturelle Situationen zu meistern (Schnabel et al., 2015). Zudem wird interkulturelle Kompetenz als multidimensionales Konstrukt verstanden, in dem multiple Kompetenzen, zusammen oder einzeln, die Qualität interkultureller Interaktion beeinflussen. Diese Kompetenzen wurden durch explorative Experteninterviews sowie durch eine ausführliche Literaturrecherche gesammelt und empirisch in einer Vorstudie untersucht. Die Ergebnisse sind in Kapitel 3 aufgeführt. Kapitel 4 beschreibt, wie der Test zur Messung Interkultureller Kompetenz (TMIK; Schnabel et al., 2015) auf Basis des Modells aus Kapitel 3 entwickelt wurde. Obwohl, in Anbetracht der Komplexität des interkulturellen Kompetenzkonstrukts, eine große Notwendigkeit besteht, mehr als eine Methode zur Messung heranzuziehen, war bislang kein validiertes multimethodales Instrument dafür verfügbar (Leung et al., 2014). Um diese Lücke zu schließen, entwickelten Schnabel et al. (2015) einen Situationsbeurteilungstest (TMIK-SJT), der eine auf Selbsteinschätzung basierende Likert-Skala (TMIK-SA) ergänzt. Kapitel 4 gibt einen Überblick über das Design und die Ergebnisse zweier Studien, von denen eine mit deutschen Studenten und die andere mit deutschen Berufstätigen durchgeführt wurde. Ich zeige, dass sowohl die durch Exploratory Structural Equation Modeling (ESEM; Asparouhov & Muthén, 2009) ermittelten Fit-Indizes für ein 17-faktorielles Modell erster Ordnung als auch jene, die durch Konfirmatorische Faktorenanalyse für das sechs-faktorielle Modell zweiter Ordnung berechnet wurden, insgesamt zufriedenstellend waren. Ergebnisse zur Konstrukt- und Kriteriumsvalidität sowie zur inkrementellen Validität des TMIK-SJT werden zudem präsentiert. Kapitel 5 stellt eine eigens entwickelte Kurzintervention vor, die dem Ansatz des Kollaborativen Assessments folgt (Fischer, 1994, 2000). Die Ergebnisse aus einer experimentellen Studie (Schnabel, Kelava, & Van de Vijver, in press) zeigen den Nutzen, der sich für ein Individuum aus der Teilnahme am TMIK mit einer anschließenden einstündigen kollaborativen Testfeedback-Intervention ergibt. Dieser Nutzen bezieht sich auf die durch Selbsteinschätzung ermittelte interkulturelle Kompetenzentwicklung, die individuelle Stufe im Transtheoretischen Modell (DiClemente & Prochaska, 1998; Prochaska, DiClemente, & Norcross, 1992), das interkulturelle Selbstvertrauen und das interkulturelle Selbstverständnis. In Kapitel 6 fasse ich zusammen, wie die, vor allem für die Personalauswahl entwickelte, Kurzversion des TMIK (TMIK-S; Schnabel, Kelava, Van de Vijver, & Seifert, 2014) in Deutschland und Brasilien validiert wurde. Die Ergebnisse der Analyse der Messmodellinvarianz (Meredith, 1993) stützen das Vorliegen eines kulturübergreifend validen Modells interkultureller Kompetenz. In Kapitel 7 diskutiere ich die zuvor genannten Themen dieser Monographie umfassend und beschreibe die zentralen Implikationen und Limitationen. Zusätzlich gebe ich einen Ausblick auf zukünftige Forschungsfragen zum Thema interkulturelle Kompetenz.